Relevance of Oral Rehydration as a Natural Method of Compensation of Fluid and Electrolyte Balance in the Body - I.B. Yershova; A.A. Mochalova; S.N. Chernousova; V.A. Khatnyuk; T.B. Kolomina (Zaslavsky O.Yu., 2012)
The article focuses on the role of oral rehydration in children. Following the WHO recommendations, the question of best solution for oral rehydration is discussed.